Pengaruh Kompensasi Dan Pengalaman Kerja Terhadap Etos Kerja Islami Karyawan Bank Syariah Mandiri Kantor Cabang Rogojampi Kabupaten Banyuwangi - Nurul Inayah; Nawal Ika Susanti; Rahmania Ika Putri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Research with the title Influence of Compensation and Work Experience on Islamic Work Ethics of Bank Syariah Mandiri Employees at Rogojampi Banyuwangi Branch Office. With the aim to find out whether compensation influences and Work Experience affects the Islamic work ethic of employees, whether work experience affects the Islamic work ethic of Bank Syariah Mandiri Employees at Rogojampi. So it can be concluded that compensation does not significantly influence the Islamic Work Ethic, which means that Ho is accepted with a sig value of 0.147 and Work Experience has a significant effect on the Islamic Work Ethic, which means Ha is accepted with a sig value of 0,000. And the (silmutan) compensation variable (X1) and work experience variable (X2) have a very strong attachment with a value of 84,397 with a significance level of 0,000 <0.05 then Ha is accepted. The coefficient of determination (R2) is 0.862 which means that the compensation and work experience variables influence the Islamic work ethic of employees by 86.2% and the remaining 13.8% is influenced by other variables outside this study.